2017
DOI: 10.1016/j.devcel.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Atg5 Disassociates the V1V0-ATPase to Promote Exosome Production and Tumor Metastasis Independent of Canonical Macroautophagy

Abstract: Autophagy and autophagy-related genes (Atg) have been attributed prominent roles in tumorigenesis, tumor growth, and metastasis. Extracellular vesicles called exosomes are also implicated in cancer metastasis. Here, we demonstrate that exosome production is strongly reduced in cells lacking Atg5 and Atg16L1, but this is independent of Atg7 and canonical autophagy. Atg5 specifically decreases acidification of late endosomes where exosomes are produced, disrupting the acidifying VV-ATPase by removing a regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
212
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(217 citation statements)
references
References 66 publications
5
212
0
Order By: Relevance
“…This leads us to propose a model departing from the conventional views of how LC3 or other mAtg8s work in autophagy, suggesting a new mechanism of control of membrane trafficking/ fusion through direct action of mAtg8s on SNARE molecules ( Fig 7F). These include (i) mAtg8 binding to autophagic receptors from the SLR (Birgisdottir et al, 2013;Rogov et al, 2014) (Florey et al, 2015), MVB/exosome formation (Guo et al, 2017), and via binding to TECPR2 in the COPII-dependent ER export . This amends the conventional view of mAtg8s expanding the autophagosomal membranes (Carlsson & Simonsen, 2015) and complements more recent views of mAtg8s working in the recruitment of various components of the autophagic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to propose a model departing from the conventional views of how LC3 or other mAtg8s work in autophagy, suggesting a new mechanism of control of membrane trafficking/ fusion through direct action of mAtg8s on SNARE molecules ( Fig 7F). These include (i) mAtg8 binding to autophagic receptors from the SLR (Birgisdottir et al, 2013;Rogov et al, 2014) (Florey et al, 2015), MVB/exosome formation (Guo et al, 2017), and via binding to TECPR2 in the COPII-dependent ER export . This amends the conventional view of mAtg8s expanding the autophagosomal membranes (Carlsson & Simonsen, 2015) and complements more recent views of mAtg8s working in the recruitment of various components of the autophagic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially reported that exosome production by the spleen‐derived murine DC line D1 was lower when activated by lipopolysaccharide, as confirmed using bone marrow‐derived DCs and monocyte‐derived DCs . This might appear to be contradictory with regard to the lower activity of the vacuolar proton pump (V‐ATPase) in immature compared to mature DCs, and thus for which lower exosome secretion could be expected, as recently noted for other cell types . However, DCs also release vesicles from the plasma membrane that have a protein composition close to that of exosomes, including MHC class II, and could constitute the major part of vesicles released by immature DCs .…”
Section: Exosomes and Differentiationmentioning
confidence: 97%
“…Lysosome inhibitors such as chloroquine or bafilomycin A1 have been shown to increase exosome release. Moreover, it was demonstrated that Atg5 dissociates V 1 V 0 ‐ATPase in endosomes, in turn decreasing endosomal acidification and promoting exosome secretion . It is thus tempting to speculate on mutual compensation between the two pathways.…”
Section: Similarities Between Degradative and Secretory Mvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although V‐ATPase inhibition can result in increased autophagic markers in some settings,74 V‐ATPase is required for activation of noncanonical autophagy 83. In a very recent study, the autophagy‐related protein ATG5 was demonstrated to displace ATP6V1E1 from V‐ATPase, causing it to accumulate in exosomes 84. The function of autophagy in cancer is also complex; both pro‐survival and pro‐death rolls have been described, dependent on cellular context 85…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetmentioning
confidence: 99%